Performance Evaluation of Application Layer Protocols in Internet Of Things IOT - حجازية محمد; حمامي نهى (Latakia University Journal -Engineering Sciences Series, 2020)
The emerging technologies of the Internet Of Things (IOT) offer a new opening in the world of applications, as it affects the quality of life in a revolutionary way, as it interferes with various fields such as health care, environmental monitoring, military and economic fields, industrial automation and many other fields. The communication everywhere is one of the critical requirements in the Internet of things, so several suitable communication protocols have recently been developed. And its study is one of the most important fields that research have been interested in recently. Hence the importance of this research lies in the study of performance of the newly developed Coap and Mqtt protocols within the application layer, which can be used in various applications of Internet of Things. The research also draws necessary recommendations and suggestions for the selection of the most appropriate protocol in terms of performance.This has been done by proposing appropriate scenarios for IoT applications to perform experiment that is similar to the working conditions of this protocols in the applied field to study the impact of a set of different parameters on the performance and behavior of protocols, Specifically the size of sent message , reliability levels of protocols, and the time interval applied between sent messages. performance was evaluated based on the basic parameters in such protocols, such as size of the data exchanged and overhead and efficiency and end to end delay . The study found a set of recommendations regarding choosing the most suitable protocol for work.